Influencing of E-Commerce Website Towards Young Adult Customer Purchase Decision In Jakarta Area - Sonny Vin Sudtejo; Fajar Putra Ryanda; Kezia Sugiarto; Putri Asri Azizah (President University, 2017)
The online shopping in Indonesia from year to year has increased rapidly. Consumers often do online shopping is a group of young adults in the big cities. Jakarta is a city that many young adult doing shopping online. Base on the pre-survey, researchers found that Online shopping experience is not always pleasant. Consumers often experience disappointment for many reasons, such as data security issues, payment, web design, product quality and delivery of goods. Research was conducted online by using google docs. The number of respondents in this study as many as 136. Questionnaire results were processed using SPSS version 20. The results show that there is a positive and significant effect payment and web design on purchased decision. Keywords: E-commerce, wed design, product, payment, purchase decision